2014
DOI: 10.1088/0960-1317/24/5/055014
|View full text |Cite
|
Sign up to set email alerts
|

High performance dual-wave mode flexible surface acoustic wave resonators for UV light sensing

Abstract: Dual-mode flexible ZnO/polyimide surface acoustic wave (SAW)-based ultraviolet (UV) light sensors were fabricated and their performance was investigated. UV light sensing measurements showed that the responses of the dual wave modes of the sensors increase with the increase of light intensity and the frequency changes linearly with the change of light intensity. Under a 4.5 mW cm−2 UV light illumination, the resonant frequency of the Rayleigh wave decreased up to ∼43 kHz, while that of the Lamb wave was approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…SAW devices are usually fabricated on rigid substrates such as silicon, quartz, LiNbO3 [11], and LiTaO3 [12], which are not suitable to fabricate flexible SAW devices. It was reported that polymers could be used as the flexible substrates for fabrication of bendable or flexible SAW devices [13], and some results about humidity sensing [14] and UV sensing [15] have been published. However, because of significant attenuation and dissipation of acoustic wave and energies, poor film crystallinity and poor adhesion of thin film on the polymer substrates, there are significant challenges to realize efficient acoustic microfluidics and high precision sensing functions using these polymer substrates [16].…”
Section: Introductionmentioning
confidence: 99%
“…SAW devices are usually fabricated on rigid substrates such as silicon, quartz, LiNbO3 [11], and LiTaO3 [12], which are not suitable to fabricate flexible SAW devices. It was reported that polymers could be used as the flexible substrates for fabrication of bendable or flexible SAW devices [13], and some results about humidity sensing [14] and UV sensing [15] have been published. However, because of significant attenuation and dissipation of acoustic wave and energies, poor film crystallinity and poor adhesion of thin film on the polymer substrates, there are significant challenges to realize efficient acoustic microfluidics and high precision sensing functions using these polymer substrates [16].…”
Section: Introductionmentioning
confidence: 99%
“…The photo-generated carriers are confined in the surface layer of ZnO, resulting in an increase in the surface sheet conductivity, σ s . The relationship between the surface conductivity and acoustic wave velocity, ν , in the ZnO surface layer is given in the equation below 21 22 23 24 ,…”
Section: Discussionmentioning
confidence: 99%
“…The much better intrinsic Allan deviation proves that the oscillator performance can be improved through future engineering. Table I shows metrics benchmarking of this work with previously reported resonant UV detectors, including thin film bulk acoustic resonators (FBAR) and surface acoustic wave (SAW) devices using ZnO or AlGaN [20,21,22]. The β-Ga 2 O 3 oscillator shows much better performance in both || and MDP.…”
Section: Introductionmentioning
confidence: 94%